Completed suicide in adults of rural Kerala: Rates and determinants - C. SAUVAGET, K. RAMADAS, J. M. FAYETTE, G. THOMAS, S. THARA, R. SANKARANARAYANAN (THE NATIONAL MEDICAL JOURNAL OF INDIA, 2009)
Background. India has witnessed a dramatic increase in suicide rates during the past few decades. The southern state of Kerala has been reporting the highest rates of suicide. Since suicide rates are estimated from death registries, they are likely to be under-reported because the civil registration system is incomplete and suicide deaths are poorly reported. Methods. A cohort of 132 000 participants (age 35 years and above) in Thiruvananthapuram (erstwhile Trivandrum) district, Kerala was followed up for mortality from 1996 to 2005, after having filled-in a lifestyle questionnaire at baseline. The cause of death was based on verbal autopsy. Suicide methods were recorded and rates were estimated, and suicide risks were calculated according to several socioeconomic factors. Results. During the follow up period, a total of 11 608 deaths, of which 385 were suicides (3.3% of total deaths), were registered. The overall suicide rate was 39.3/100 000 person-years among adults 35–90 years of age (men: 78/ 100 000; women: 16.5/100 000). The predominant methods of suicide were hanging, followed by poisoning and drowning. The suicide determinants were male gender, middle- age (40–60 years), Hindu, alcohol drinkers and secondary education level (<7 years). Neither low socioeconomic level, living alone, nor being a married woman was associated with suicide risk. Conclusion. Suicide rates were consistent with the official rates of Thiruvananthapuram district (37/100 000). However, our study population did not include the 14–34-year-old age- group which represents more than 37% of all suicides and hence it is more likely that the official rates are under-reported Determinants of suicide were in line with previous studies.